Simulasi traffic dan performa jaringan SDN menggunakan ONOS Controller dan standar TIPHON - Agus, Yulius Manahil Hendrawan; Sulistyo, Wiwin (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
The increasing number of devices connected to the network and the rapid growth of data traffic have posed challenges in managing conventional networks. Traditional networks often experience inefficiencies in handling high traffic loads due to static traffic management, leading to congestion in some network paths while others remain underutilized. Software-Defined Networking (SDN) has emerged as an innovative solution by separating the control plane and data plane, enabling more flexible, centralized, and programmable network management. This study evaluates the performance of OpenFlow-based SDN using the ONOS Controller and compares it with conventional home Wi-Fi networks based on the TIPHON standard. The simulation was conducted using Virtual Machines (VMWare) and Mininet, which were connected to the ONOS Controller via the OpenFlow protocol, while the conventional network testing was performed using the Command Prompt. The testing included three data transmission scenarios: 1 host to 1 host, 2 hosts to 1 host, and 2 hosts to 2 hosts simultaneously, with measured parameters including delay and packet loss. The results indicate that in the 1 host to 1 host scenario, both SDN and conventional networks had a delay of less than 150 ms and 0% packet loss. However, in the 2 hosts to 2 hosts scenario, the conventional network experienced an increase in delay and packet loss of up to 17%, whereas SDN remained stable with a delay below 150 ms and 0% packet loss. This confirms SDN's superior efficiency in handling high network traffic through more dynamic traffic distribution. Additionally, this study confirms that SDN's centralized control allows for more adaptive traffic management, reduces congestion, and improves overall network stability. These research demonstrate SDN's efficiency in handling high traffic loads, making it a superior solution for modern network demands.